Determinants affecting financial literacy among selected employees in Kowamas Berhad / Siti Nor Amirah Md. Noh - Md. Noh, Siti Nor Amirah (Faculty of Business and Management, 2019)
In current world today, more credit is granted to consumer as one of alternative for their purchasing. Therefore, they feel comfortable with their situation and using it without thinking what will happen if they cannot pay for the credit in future. The objective of this paper was to find out about what is the determinate that will affect financial literacy. Determinants affecting financial literacy was purposed based on the previous studies to examine the relationship between financial attitude, financial behaviour and financial knowledge towards financial literacy among selected employees in Kowamas Berhad. Total 101 sample of respondent data has been recorded and being analysis for this study. Data has been analysing by using Statistic Package for Social Science (SPSS). Regression and correlation are use in this study to analyse the relationship between independent variables toward dependent variable. Results indicate that all variables have positive effect towards dependent variables